Challenging prospects for roam like at home - Georgios Petropoulos; J. Scott Marcus (Bruegel, 2016)
On 25 November 2015, the European Union enacted new rules for international mobile roaming (IMR) under Regulation 2015/2120, which seeks to implement a Roam Like at Home (RLAH) regime among the member states of the European Union. Questions remain, however, as to whether it is possible to implement RLAH without mandating below-cost pricing and thus introducing significant regulatory and economic distortions. It is difficult to see how RLAH could be implemented for other than trivial amounts of IMR traffic without significant cross-subsidisation of the IMR service in many different dimensions. Identifying ways to maintain the ubiquity of the IMR service without unduly distorting the economics of European mobile markets and networks would appear to pose serious challenges; the saving grace, however, might well be that IMR revenue now represents a small enough fraction of total mobile revenue (thanks to previous regulation) that the necessary cross-subsidies might be manageable. The European Commission, which is required to assess the situation and to provide legislative proposals by 15 June 2016, faces a daunting task.
Keywords: 330; Mobilkommunikation; International; Telekommunikationspreis; Preisregulierung; Telekommunikationspolitik; EU-Staaten